PENGARUH STRUKTUR KEPEMILIKAN, KUALITAS AUDIT DAN UKURAN PERUSAHAAN TERHADAP TRANSPARANSI INFORMASI (Studi Empiris pada 100 Perusahaan Publik Terbesar di Indonesia) - Ria Nelly Sari; Rita Anugerah; Rhia Dwiningsih (Program Studi Pendidikan Ekonomi Universitas Riau, 2012)
This paper aims to examine the effect of ownership structure, audit quality andcompany size on transparency of information. Seventy-three large public firms from100 largest companies rated by SWA 2008 were selected as the sample.Transparency is indexed by the extent to which companies disclose the voluntaryinformation in their annual report for the year 2005-2007. A panel data set of 219firm year observations is analyzed. Results demonstrate that company size do effectthe transparency of information. From three types of ownership structure onlyforeign ownership has significant effect on transparency of information. Thediscussion and implications of the findings and suggestion for future research arediscussed.